MicroRNAs as biomarkers of harmful environmental and occupational exposures: a systematic review - Kotsyfakis, Michail; Patelarou, Evridiki (Biomarkers, 2019)
Environmental exposure is a growing public health burden associated with several negative health effects. An estimated 4.2 million deaths occur each year from ambient air pollution alone. Biomarkers that reflect specific exposures have the potential to measure the real integrated internal dose from all routes of complex environmental exposure. MicroRNAs (miRNAs), small non-coding RNAs that regulate gene expression, have been studied as biomarkers in various diseases and have also shown potential as environmental exposure biomarkers. Here, we review the available human epidemiological and experimental evidence of miRNA expression changes in response to specific environmental exposures including airborne particulate matter. In doing so, we establish that miRNA exposure biomarker development remains in its infancy and future studies will need to carefully consider biological and analytical 'design rules' in order to facilitate clinical translation.
Keywords: Environmental Exposure; biomarker; mikro RNA; microRNA; organic compounds; pracovní expozice; particulate matter; MicroRNAs; heavy metals; biologické markery; environmental exposure; lidé; Air pollution; Occupational Exposure; Humans; Biomarkers; vystavení vlivu životního prostředí